Effects of sprint training combined with vegetarian or mixed diet on muscle carnosine content and buffering capacity - Baguet, Audrey; Everaert, Inge; De Naeyer, Hélène; Reyngoudt, Harmen; Stegen, Sanne; Beeckman, Sam; Achten, Eric; Vanhee, Lander; Volkaert, Anneke; Petrovic, Mirko; Taes, Youri; Derave, Wim (European journal of applied physiology, 2011)
Carnosine is an abundant dipeptide in human skeletal muscle with proton buffering capacity. There is controversy as to whether training can increase muscle carnosine and thereby provide a mechanism for increased buffering capacity. This study investigated the effects of 5 weeks sprint training combined with a vegetarian or mixed diet on muscle carnosine, carnosine synthase mRNA expression and muscle buffering capacity. Twenty omnivorous subjects participated in a 5 week sprint training intervention (2–3 times per week). They were randomized into a vegetarian and mixed diet group. Measurements (before and after the intervention period) included carnosine content in soleus, gastrocnemius lateralis and tibialis anterior by proton magnetic resonance spectroscopy ( 1 H-MRS), true-cut biopsy of the gastrocnemius lateralis to determine in vitro non-bicarbonate muscle buffering capacity, carnosine content (HPLC method) and carnosine synthase (CARNS) mRNA expression and 6 × 6 s repeated sprint ability (RSA) test. There was a significant diet × training interaction in soleus carnosine content, which was non-significantly increased (+11%) with mixed diet and non-significantly decreased (−9%) with vegetarian diet. Carnosine content in other muscles and gastrocnemius buffer capacity were not influenced by training. CARNS mRNA expression was independent of training, but decreased significantly in the vegetarian group. The performance during the RSA test improved by training, without difference between groups. We found a positive correlation ( r = 0.517; p = 0.002) between an invasive and non-invasive method for muscle carnosine quantification. In conclusion, this study shows that 5 weeks sprint training has no effect on the muscle carnosine content and carnosine synthase mRNA.